Policing the mentally ill : making sense of links in the chain of interagency collaboration in the community : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Palmerston North, New Zealand - Denne, Stephanie (Massey University, 2010)
The shift to community care through the deinstitutionalisation movement in New Zealand has been criticised for producing fragmented and uncoordinated service provision for those with mental illness in the community. As a result, the police are coming into increased contact with the mentally ill, often in times of crisis, positioning police at the junction between mental health services and the criminal justice system. Barriers to access for integrative, comprehensive mental health care in the community have led to police understanding their position as the ‘ambulance at the bottom of the cliff’. While previous research has attended to police officer attitudes and points of interaction with those with mental illness in the community, little has been said regarding understandings of the collaborative relationships from the vantage point of those officers policing the mentally ill. The current research sought to address this gap in the literature by exploring how police make sense of their experiences with those with mental illness in the community using a Foucaultian form of discourse analysis. The discourses that co-articulated and produced understandings of the position(s) of police in community service provision for the mentally ill and the power relationships between the police, the mental health system and the mentally ill can be understood through ‘links in the chain’; ‘the (un) identifiable other’; ‘no-man’s land’; ‘underdogs’; and ‘the cure’. These systems of meaning making from the police vantage point reproduced and re-institutionalised constructions of the mentally ill as ‘criminal’ or ‘disordered’, necessitating mechanisms of power and control to address the ‘risk’ mental illness posed to the community. Through such understandings the police, as society’s institutional response to ‘threat’, necessarily occupy the position of the ‘ambulance at the bottom of the cliff’ at the institutional boundaries between disorder and criminality. And it is here that the institutional response to mental illness re-emerges as re-institutionalisation.
Keywords: Mentally ill; Police; Mental health; New Zealand; Fields of Research::380000 Behavioural and Cognitive Sciences::380100 Psychology::380105 Social and community psychology